Sosialisasi Digital Enterpreneurship bagi Generasi Milenial pada Siswa/Siswi SMKN 9 Jakarta (Neolectura, 2023)
Currently, the global industrial world has entered a new era which is often referred to as the Industrial Revolution 4.0 or also known as the Digital Era 4.0. The digital era 4.0 shows how important it is to increase competence in technology. Technology that is developing so fast requires the millennial generation to use it not only for consumptive activities but also to generate income for themselves and others. The difficult times in the past few years have hit Indonesia's economy hard. This can be seen in the large number of unemployed caused by restrictions on the number of workers during the COVID-19 pandemic. The millennial generation, which is considered quick to respond to change and master technology, is expected to continue to increase their entrepreneurial knowledge and skills (entrepreneurship). This digital entrepreneurship socialization activity is expected to increase the knowledge and skills of students of SMK N 9 Jakarta so that they can empower themselves and those around them. The method used in this socialization was to make preparations by contacting the school, implementing socialization by presenting material, and evaluating through filling out questionnaires by participants. From the presentation explained by the speakers, both in terms of theory and practice of giving business ideas to the steps to starting a business, the participants seemed enthusiastic about participating in this event even with all the limitations during implementation. This can be seen in the questions that arose after the material presentation session.